STUDI KEKUATAN TARIK, KEKERASAN, DAN STRUKTUR MAKRO PADA HASIL PENGELASAN SMAW MATERIAL BAJA KARBON RENDAH MENGGUNAKAN E6013 DENGAN PENAMBAHAN KROM - Setyo Firman Alamsyah (Jurnal Pendidikan Teknik dan Vokasional, 2022)
This study aims to determine the effect of adding chromium to the SMAW process on the tensile strength, hardness value and macro structure of low carbon steel welded joints. The welding process in this study used the E6013 electrode with the addition of chrome and welding without the addition of chrome to compare the results of tensile tests, hardness tests and macro structures. After the welding process, continued with the manufacture of tensile test specimens with 3 specimens each for each variation, the manufacture of hard test specimens and macro structures. In the tensile test results, the tensile strength values ​​between specimens with the addition of chromium and without the addition of chromium (non) did not show a significant difference, the average tensile strength values ​​were 38.33 kg/mm² and 38.67 kg/mm², respectively. The addition of chrome to the SMAW process has been shown to have an effect on the hardness value of low carbon steel welded joints. The hardness value of the specimen with the addition of chrome is greater with an average hardness value of 166.8 VHN in the weld metal area than the specimen without the addition of chromium (non) with an average hardness value of 150.97 VHN. In the macro structure, between the specimens with the addition of chromium and without the addition of chromium (non) there was no porosity.